Gwarant w sytuacjach kryzysowych producentów części i podzespołów środków transportu rolniczego - poziom wiedzy i zakres kompetencji doradcy restrukturyzacyjnego = Guarantee in crisis situations for parts manufacturers and components of agricultural transport means - level of knowledge and scope of competences restructuring advisor - Niewiadomski, Przemysław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the article is to show the competences of a modern restructuring advisor. The author found it justified to specify the role, place or knowledge and methods of obtaining it by restructuring advisors. The main goal was achieved by formulating partial goals, which the author includes: identification of areas of knowledge of a modern restructuring advisor based on the tasks and responsibilities he performs; presenting and discussing the rules for obtaining qualifications by restructuring advisors reflecting the criterion of their excellence.
Keywords: sytuacje kryzysowe przedsiębiorstw; kompetencje; doradca restrukturyzacyjny; crisis situations of enterprises; competences; restructuring advisor